Do impresso ao digital: o texto jornalístico em mutação - Freitas, Carla Miranda B. de (2010)
The development of web journalism or cyber journalism resulted in a change of route for traditional newspapers. The text structure, the approach of the subjects and even the role of the newspapers are under revision at this moment. On the other hand, there are also significant changes in news writing for the Internet. If, at first, the companies were limited to simply replicate for the Internet the content published in the newspapers, just transposing for the new medium the narrative techniques from the print journalism, the text for the web, in its following stages, started to acquire independence and to develop itself towards what would be considered its ideal form. This dissertation intends to examine the major changes in newspapers text after the emergence of the so-called cyber journalism and also aims to show the evolution process of the text written exclusively for the web. The starting point for the research is the analysis and comparison of texts from the newspaper O Estado de S. Paulo, in both printed and digital versions, and also from other selected examples in national and international press that helps to clarify these changes. The foundations of this study are: the theory of the creation process developed by Cecilia Salles, the theories of media presented by Jay David Bolter and Richard Grusin (Remediation: Understanding New Media), and studies conducted by researchers specialized in journalistic texts such as Ramón Salaverria, Concepción Edo and John Canavilhas